Collectivism and continuity: a ceramic composition as a metaphorical persuasion for extended family cohesion - Charles Dogbeda Melos Vicku; Samuel Nii Adamah Sampah; Robert Amoanyi; Ebenezer Fiifi Mensah; Ansah-Asiedu Jnr (Cogent Arts & Humanities)
The extended family system in the Ghanaian culture is akin to the growth of a gourd or calabash vine. This parallel assertion underpins the common bond and belonging of family members, emphasizing the necessity of mutual responsibility, care, and cooperation. Each gourd contributes to the vine’s health, just as each family member contributes to the well-being and stability of the extended family. The basic concept of this study is to depict the extended family system philosophically utilizing various bottle types. The study utilised a qualitative research approach and a descriptive research design with Marshall’s Aesthetico Action research cycle. To maintain consistent supplies of these bottles, a one-of-a-kind mould was constructed using one original bottle as a template. The tangible conceptual artistic composition was created by combining clay, iron rods in the form of metallic rings, acrylic paints, and glazes. Their composition highlights the contrasts in resilience, temperament, charm, perspective, affluence, age, intrinsic attributes, and other characteristics among extended family members and stresses the underlying cohesiveness. Results revealed that art in the form of ceramic sculpture composition can serve as a conduit pipe to establishing family standards of identity, loyalty, and responsibility; thus projecting the significance of artistry in socio-cultural dynamics.